THE SIGNIFICANCE OF HOME CONFINEMENT IN PLANNINTG OF THE HEALTH CARE DELIVERY SYSTEM IN THE RURAL AREAS OF IRAN - B. Nikpour (Tehran University of Medical Sciences, 1981)
The objective of this study has been to examine the relationship between home and the hospital confinement in the treatment of serious illness and the impact of such phenomena on the pattern of the delivery of health care in the rural areas. In this study a total of 10,248 inhabitants of 11 villages in Isphahan (Mobarakeh area) were studied during a six months period between March and September of 1976. As the results of this study show, the total of 4,446 cases of more than 4 days of home confinement at hope per year in comparison with 430 cases of hospital confinement during the same period indicates a ten fold preference for home care. Further investigations show that although the availability of hospital care has been an important factor for such distribution, the belief of rural population and cultural considerations has also played a significant role. Thus, although further in depth investigation on the technical advantages of home confinement in comparison with hospital confinement is indicated, such a pattern can be of value to the planners in designing the net work of the health care delivery system for the planners in designing the net work of the health care delivery system for the rural areas of Iran.